Characteristic of multiple-antibiotic-resistant \( Salmonella enteritica \) from Muscovy duck in Hanoi - Nguyen, Trung; Le, Hoa; Ta, Yen; Pham, Da; Nguyen, Nam; Nguyen, Hoang (Academia Journal of Biology, 2022)
Nowadays, as the global population grows, the demand for food is also becoming higher each day. Together with the rise in food demand, Muscovy duck has been gradually bred industrially as a poultry food supply along with the chicken. The change from traditional to industrial breeding poses a potential risk of pathogenic bacteria infection and antimicrobial resistance bacteria. Especially Salmonella, one of the leading pathogens worldwide, is also notable for its antimicrobial resistance. In this study, by using Muscovy duck carcasses collected from wet markets in 05 districts in Ha Noi, we assessed the rate of Salmonella infection at first, then conducted an antibiotic susceptibility test utilizing 15 types of antibiotics, from then whole genome sequencing was applied for 8 multidrug resistant isolates. Next, the genomic data after successfully sequenced was used for analyzing antibiotic resistance genes, genotypes, multi-locus sequence-based typing (MLST), virulence factors, and plasmids. 65% of Muscovy duck samples were positive for Salmonella, in which 95% (19/20 strains) of Salmonella isolated was multidrug resistant. The result of the antibiotics susceptibility test indicated that phenotypic resistance to ampicillin was the most observed (92.3%, 19/20), followed by tetracycline (90%, 18/20), cefuroxime (85%, 17/20), cefazolin (85%, 17/20), ceftriaxone (85%, 17/20), Cefotaxime (85%, 17/20), trimethoprim (70%, 14/20), gentamicin (60%, 12/20), chloramphenicol (55%, 11/20), nalidixic acid (55%, 11/20), ceftazidime (50%, 10/20), ciprofloxacin (2/20). However, all isolates were susceptible to cefoxitin and meropenem. Sixty-five antibiotic resistance genes were identified, including genes that are resistant to aminoglycoside, 3rd generation antibiotics (cefotaxime, cefoperazone, ceftizoxime, ceftazidime, ceftriaxone, etc.). Col, IncA plasmids and some mobile genetic elements were identified. Simultaneously Salmonella pathogenic islands were found in all sequenced strains, exclusively SPI 1, SPI 3, and SPI 9 were carried in every isolate.